(untitled) (Tạp chí Y học Cộng đồng, 2025)
Objective: This study was conducted to assess the level of compliance and effectiveness of food safety and hygiene (FSH) procedures at the kitchen of Level-2 Field Hospital No. 6 (L.2FHN.6) in Bentiu, South Sudan. Subjects and Methods: The study employed a cross-sectional descriptive design. The subjects included the entire system of processes related to food hygiene and safety at the kitchen of L.2FHN.6, observed from January 1 to April 30, 2025. Results: All 24 kitchen staff members achieved 100% compliance in all personal hygiene criteria. In the food preparation and processing group, two criteria — “no cross-contamination between raw and cooked food” and “separate zones and utensils for raw and cooked food”-reached 100% compliance. In contrast, “retaining food samples” had 0% compliance, indicating a significant shortcoming. Regarding cold storage, three criteria achieved full compliance, while refrigerator stability reached 91.67%. For input material management, three out of four criteria were met (100%), with visual inspection of incoming goods slightly lower (95.83%). Food consumption behavior and pest control achieved 100% compliance across all five evaluated criteria. Conclusion: The results confirm high compliance levels in personal hygiene, food storage, and pest control at L.2FHN.6. However, notable issues remain in retaining post-processing food samples and stabilizing the cold chain to ensure overall food safety.